Design and implementation of interactive multimedia application for increased learning for virtual studio lighting tutorials - Sayed Mothar, Syaripah Mohaizah; Zainal, Azlan; Padil, Md. Nagib (2012)
This research describes the design and implementation of virtual interactive multimedia design applications to be used mainly by photography students to increase their understanding of basic lighting course. In education, traditional teaching and learning is no longer the order of the day. In line with this development in technology the researchers sets out to investigate what are the implications of virtual tutorial in studio lighting subject of the Diploma and Creative Imaging in Photography program in Universiti Teknologi Mara. It is believed that the Virtual Tutorials are effective in promoting teaching and learning among the students. The applications named a virtual studio lighting tutorials. The researchers have covered of all the topics that include in the studio lighting subject for photography students. The topics are Direction of Light, High Key lighting, Low Key Lighting and lighting for glassware. This application expose students to focus better. According to research conducted, students remember better the contents and information when it's represented and learned both visually and verbally in interactive way. The lacks of visual educational in interactive multimedia tutorial materials that support the delivery of teaching in classroom for the photography students create barriers to effective teaching and learning. For this reason the virtual studio tutorials is chosen to overcome the problem. Neo Mai & Ken Neo TK, (1998) pointed out that the uses of multimedia technology are an innovative and effective teaching and learning strategy. The researchers have set to conduct and investigate how to create a fun, interactive, easily understood, available and efficient way for students in the diploma level to use various tutorial simulations of basic studio lighting. Against this backdrop the researchers sets to measure if the students and lecturers find it effective to use the multimedia as an effective learning and teaching tool for the photography department. The results are that both the students and lecturers find that the virtual tutorial is effective compared to the conventional method. It was also very well received by the respondents. Many students responded saying it helped them with the understanding of the subject matter in studio lighting. For many others the virtual tutorial helped them to remember the subject. All in all the students were able to apply the lesson studied rather than memorize it. For the lecturers it was equally good as it reduces their time to teach as the students understand better and faster with the Virtual Tutorial.